(untitled) (Research, Society and Development, 2020)
In the scenario of discussions about the didactic and epistemological obstacles that ’haunt’ the teaching and learning processes of Mathematics content in Elementary School in the early years, we find among other Santos theorists (2007; 2014; 2015; 2017). In this study, we aim to present the importance of challenging the Pedagogy graduate to leave his ’comfort zone’, where he reproduces the mathematical contents/models, and provoke him to deconstruct/reconstruct/discover the mathematical concepts, to the detriment of a paralytic reproduction, and thus, we contribute to the thinking/questioning, from challenging situations. This practice has also contributed to the pedagogist’s perception that his knowledge must exceed that of the student; and, above all, it has made it possible for the pedagogist to reflect more on his praxis, in order to constitute himself within the process as an epistemic subject, providing him with a rethinking of his action in a vision of what it is to teach. The actions have awakened us to the need for a more innovative teaching formation that overcomes challenges and difficulties in the exercise of teaching with excellence.